Modeling of Zymomonas mobilis central metabolism for novel metabolic engineering strategies - Kalnenieks, Uldis; Pentjuss, Agris; Rutkis, Reinis; Stalidzans, Egils; Fell, David A. (Frontiers in Microbiology, 2014)
Mathematical modeling of metabolism is essential for rational metabolic engineering. The present work focuses on several types of modeling approach to quantitative understanding of central metabolic network and energetics in the bioethanol-producing bacterium Zymomonas mobilis. Combined use of Flux Balance, Elementary Flux Mode and thermodynamic analysis of its central metabolism, together with dynamic modeling of the core catabolic pathways, can help to design novel substrate and product pathways by systematically analysing the solution space for metabolic engineering, and yields insights into the function of metabolic network, hardly achievable without applying modeling tools.